2013
DOI: 10.1128/jvi.03388-12
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Phosphorylation of the Triple Gene Block Protein 3 Regulates Cell-to-Cell Movement and Protein Interactions of Potato Mop-Top Virus

Abstract: Functions of viral proteins can be regulated through phosphorylation by serine/threonine kinases in plants, but little is known about the involvement of tyrosine kinases in plant virus infection. In this study, TGBp3, one of the three movement proteins encoded by a triple gene block (TGB) of Potato mop-top virus (PMTV), was detected for the first time in PMTV-infected plants and found to be tyrosine phosphorylated. Phosphorylation sites (Tyr 87-89 and Tyr 120 ) were located in two amino acid motifs conserved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…Although some plant proteins are also modified by both phosphorylation and O-GlcNAcylation (Chen et al, 2005;Taoka et al, 2007;Xing et al, 2009;Xu et al, 2017;Zentella et al, 2016), the interplay of these PTMs in plants is largely unknown. Although several proteins of plant viruses are known to be phosphorylated (Champagne et al, 2007;Hoover et al, 2016;Hu et al, 2015;Hung et al, 2014;Ivanov et al, 2003;Jakubiec et al, 2006;Lee and Lucas, 2001;Link et al, 2011;M odena et al, 2008;Puustinen et al, 2002;Samuilova et al, 2013;Shapka et al, 2005;Zhao et al, 2015), there is evidence that the CP of the potyvirus PPV is both phosphorylated and O-GlcNAcylated (Chen et al, 2005;Fern andez-Fern andez et al, 2002;Subr et al, 2007); this makes this protein an excellent model to study how phosphorylation and O-GlcNAcylation jointly regulate protein activity in plant cells and to define the roles of these PTMs in viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…Although some plant proteins are also modified by both phosphorylation and O-GlcNAcylation (Chen et al, 2005;Taoka et al, 2007;Xing et al, 2009;Xu et al, 2017;Zentella et al, 2016), the interplay of these PTMs in plants is largely unknown. Although several proteins of plant viruses are known to be phosphorylated (Champagne et al, 2007;Hoover et al, 2016;Hu et al, 2015;Hung et al, 2014;Ivanov et al, 2003;Jakubiec et al, 2006;Lee and Lucas, 2001;Link et al, 2011;M odena et al, 2008;Puustinen et al, 2002;Samuilova et al, 2013;Shapka et al, 2005;Zhao et al, 2015), there is evidence that the CP of the potyvirus PPV is both phosphorylated and O-GlcNAcylated (Chen et al, 2005;Fern andez-Fern andez et al, 2002;Subr et al, 2007); this makes this protein an excellent model to study how phosphorylation and O-GlcNAcylation jointly regulate protein activity in plant cells and to define the roles of these PTMs in viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, overexpression of SnRK1 in N. benthamiana plants attenuates virus symptoms and decreases viral DNA accumulation during Y10A/␤ infection, whereas knockdown of SnRK1 results in the reciprocal effects (27). However, little is known about the importance of Tyr phosphorylation of geminivirus proteins, with the exception that Tyr phosphorylation of a pomovirus MP impairs its cell-to-cell movement in plants (53). In this study, we identified two Tyr residues in TYLCCNB-␤C1 that are phosphorylated by SnRK1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, early studies on Tobacco mosaic virus (TMV) showed that its movement protein (MP) is phosphorylated by a cell wall‐associated kinase that facilitates viral cell‐to‐cell transport through plasmodesmata (Citovsky et al ., ; Karpova et al ., ; Waigmann et al ., ). Phosphorylation of viral movement proteins was then shown to be a common strategy that enables plant viruses to spread (Modena et al ., ; Link et al ., ; Samuilova et al ., ; Hu et al ., ). Various viral proteins with distinct functions are phosphorylated during viral infection, including RNA‐dependent RNA polymerase (RdRp) (Kim et al ., ; Jakubiec et al ., ; Jakubiec & Jupin, ), coat protein (CP) (Ivanov et al ., ; Hung et al ., ; Zhao et al ., ), and proteins that suppress RNA silencing and symptom development (Lewsey et al ., ; Shen et al ., , ; Zhong et al ., ).…”
Section: Introductionmentioning
confidence: 97%